(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2019)
A single sign can be interpreted differently by two people especially in cases of alleged history of assault or trauma. It’s very important to correlate the same with investigatory findings and complete examination. A case came to us for review with cause of death as traumatic hemorrhagic pancreatitis. After perusal of all the clinical records and autopsy report doubts were raised over the probable cause of death. The presented clinical signs lead the board to a probable different opinion.